Capital account convertibility : review of experience and implications for IMF policies - Quirk, Peter J. ...[et al] (IMF WashingtonUS, 1995)
Summarizes the main issues arising from the experiences of industrial and developing countries with capital account liberalization. Examines the IMF's treatment of capital controls in its surveillance, use of IMF resources, and technical assistance activities. Discusses specific experiences and issues relatinf to capital account liberalization